2017
DOI: 10.1016/j.ipej.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Higher defibrillation threshold in methamphetamine cardiomyopathy patients with implantable cardioverter-defibrillator

Abstract: IntroductionIdentification of patients with an increased risk of high defibrillation thresholds (DFTs) is important in planning implantable cardioverter-defibrillator (ICD) procedures. Clinical observations have suggested that patients with methamphetamine cardiomyopathy (MACMP) have significantly elevated defibrillation thresholds. We hypothesized that MACMP patients would have higher DFT thresholds than controls and would require procedural changes during ICD implantation to accommodate higher thresholds.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Compared with age and sex-matched controls, methamphetamine-associated cardiomyopathy patients receiving ICDs had a defibrillation threshold almost 10 Joules higher. 117 Similarly, studies comparing chronic cocaine users to control patients showed up to 13 joules higher defibrillation threshold in cocaine users receiving ICDs. 118,119 We observed a direct time-dependent correlation between cocaine use and failed ICD therapies.…”
Section: The Ethics Of Defibrillator Use In Patients With Stimulant U...mentioning
confidence: 98%
“…Compared with age and sex-matched controls, methamphetamine-associated cardiomyopathy patients receiving ICDs had a defibrillation threshold almost 10 Joules higher. 117 Similarly, studies comparing chronic cocaine users to control patients showed up to 13 joules higher defibrillation threshold in cocaine users receiving ICDs. 118,119 We observed a direct time-dependent correlation between cocaine use and failed ICD therapies.…”
Section: The Ethics Of Defibrillator Use In Patients With Stimulant U...mentioning
confidence: 98%
“…This might explain the higher prevalence of malignant heart rhythm disorders like ventricular tachycardia or torsades de pointes . Furthermore, fibrosis is most likely responsible for an increase in shock impedance in patients with an implantable cardioverter‐defibrillator …”
Section: Cardiac Complicationsmentioning
confidence: 99%